Public Awareness of Air Pollution and Mitigation of Its Risk - Endah Saptutyningsih; Berli Paripurna Kamiel (Warta LPM, 2022)
Purpose: This Community Partnership Program (PKM) aims to increase public awareness about the negative impacts of air pollution and how to mitigate it. Methodology: handing over air pollution monitoring tools, counseling, and planting air pollution-reducing plants. Results: the presence of counseling can increase understanding of the negative impacts of air pollution. Public awareness to mitigate the negative impact of air pollution has increased after attending counseling. For mitigating the negative impact of air pollution, the community will plant air pollution-reducing plants, service routinely their vehicle and reduce the use of vehicles. Applications/Originality/Value: This community service program is based on the results of air pollution mapping in the city of Yogyakarta. Programs to raise public awareness about health risks due to air pollution are still rare in Yogyakarta and the importance of knowledge about ways to mitigate air pollution risks.